2024
DOI: 10.3847/1538-4357/ad1183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of JWST NIRCam PSFs and Implications for AGN+host Image Decomposition

Ming-Yang 明阳 Zhuang 庄,
Yue Shen

Abstract: We present a detailed analysis of the point-spread function (PSF) of JWST NIRCam imaging in eight filters: F070W, F115W, F150W, F200W, F277W, F356W, F444W, and F480M, using publicly available data. Spatial variations in the PSF FWHM generally decrease with wavelength: the maximum and rms fractional variations are ∼20% and 5% in F070W, reduced to ∼3% and 0.6% in F444W. We compare three commonly used methods (SWarp, photutils, and PSFEx) to construct model PSFs and conclude that PSFEx delivers the best performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
3
6
0
Order By: Relevance
“…The mean relative errors of the PSFs within radii of 3 times the FWHM are 0.204, 0.158, and 0.136 for the F115W, the F200W, and the F356W bands. This result is consistent with the finding in Zhuang & Shen (2024), who suggested that the errors of NIRCam PSFs decrease toward long wavelengths.…”
Section: Psf Models and Errorssupporting
confidence: 93%
See 1 more Smart Citation
“…The mean relative errors of the PSFs within radii of 3 times the FWHM are 0.204, 0.158, and 0.136 for the F115W, the F200W, and the F356W bands. This result is consistent with the finding in Zhuang & Shen (2024), who suggested that the errors of NIRCam PSFs decrease toward long wavelengths.…”
Section: Psf Models and Errorssupporting
confidence: 93%
“…We construct PSF models using bright and unsaturated stars in the NIRCam images. This method has been found to provide accurate PSF models for quasar host galaxy detection and outperforms webbpsf (e.g., Ding et al 2022;Zhuang & Shen 2024). In this work, we use photutils 8 to build effective PSFs, which uses the algorithm described in Anderson & King (2000).…”
Section: Psf Models and Errorsmentioning
confidence: 99%
“…The point-spread function (PSF) is an essential factor in conducting the morphological fitting precisely. Previous studies use the theoretical PSFs (e.g., Suess et al 2022) based on the WebbPSF software (Perrin et al 2012(Perrin et al , 2014, those based on the software with the real images (e.g., Zhuang & Shen 2024), such as PSFEx (Bertin 2011), or natural stars (e.g., Ding et al 2022;Yang et al 2022). This study utilizes the theoretical PSFs from WebbPSF smoothed to match their radial flux profile to the median profile of natural stars of each field.…”
Section: Point-spread Functionmentioning
confidence: 99%
“…The size of the PSF convolution box was set to be larger than the total area of the input images. Since WEBBPSF only creates the simulated PSFs of JWST/NIRCam, it is necessary to test the effect of empirical PSF models, which can reflect the quality of real drizzled images (Ono et al 2023;Zhuang & Shen 2024). For this reason, we also generated empirical PSFs utilizing PSFEX (Bertin 2011) and applied them to the GALFIT analysis of the whole sample.…”
Section: Surface Photometry With Galfitmentioning
confidence: 99%
“…To test the effect of the PSF model for GALFIT, we generated new empirical PSFs with the pixel-based model using the PSFEX software, as done in Zhuang & Shen (2024). We set our configurations for selecting point sources, with the FWHM range (SAMPLE_FWHMRANGE) of 1-4 pixels for shortwavelength channels and 2-6 pixels for long-wavelength channels, the minimum S/N (SAMPLE_MINSN) of 100, and the maximum (a − b)/(a + b) value (SAMPLE_MAXELLIP) of 0.15.…”
Section: Appendix B Conversion From Three-dimensional To Two-dimensio...mentioning
confidence: 99%